A comparative study of interleaved three switch forward and interleaved two switch forward converters - Fauni, Jonathan Ross B. (2008)
The Interleaved Two Switch Forwared Topology is widely used in DC-DC power converters. The limitation to its operation is its duty cycle. This imposes limits on transformer and output choke design. A Three Switch Forward Topology is able to operate at higher duty cycle which can overcome these limitations. An Interleaved Three Switch Forward Converter was compared to an Interleaved Two Switch Forwared Converter. Both having the same devices and output choke but with the different transformer design to allow different operating duty cycles. Comparison was done on ripple characteristics, voltage stresses, efficiency and duty cycle characteristics. Results show that ripple for both input and output was lower for the new topology (US Patent No. 6707690, Issued March 2004). Measured output voltage ripple is 28.4mV lower and input voltage ripple is 15.32V lower for this topology. Voltage stresses on the switches are the same and the diode voltage stresses are subject to the difference in the transformer. Moreover, efficiency was also measured to be 1.2% higher at half-load. The drawback of the new topology is added parts count and a possible increase in EMI.